Dressing-induced hemodynamic instability in patients with heart failure: Implications for nursing care - Tae Watanabe; Kimiko Tagawa; Yu Kimura; Toshiro Kitagawa; Kiyokazu Sekikawa; Yukiko Nakano; Sanae Oriyama (PLoS ONE, 2026)
Background Heart failure (HF) restricts activities of daily living, impacting prognosis and quality of life. Dressing requires sustained upper-limb movements, postural transitions, and fine-motor tasks that may impose cardiovascular and autonomic demands, potentially informing on physiological tolerance during daily activities. Objective This observational study compared hemodynamic, autonomic, subjective, and upper-limb sensor count (ULSC) responses during dressing across HF clinical courses to characterize recovery dynamics during daily activities and identify nursing support requirements. Methods We compared healthy controls (HCs; n = 15), de novo HF (NO-HF; n = 12), and recurrent HF (R-HF; n = 12) groups. Heart rate (HR), systolic blood pressure (SBP), peripheral oxygen saturation, HR variability, Borg scale score, ULSC, dressing duration, and HR recovery (HRR) were measured at rest, during dressing, and after 20 min of recovery. Linear mixed-effects models tested group, time, and interaction. Pairwise comparisons were performed via Bonferroni adjustment. Results HR increased during and immediately post-dressing across groups, with NO-HF exhibiting higher HR than R-HF. HRR varied among groups (HC vs. NO-HF: P = 0.108; HC vs. R-HF: P < 0.0001; NO-HF vs. R-HF: P = 0.026). SBP displayed a group effect (P = 0.034). Peak HR responses tended to occur immediately post-dressing in HC and NO-HF, whereas R-HF descriptively showed a delayed peak around 5 min. No significant group × time interaction was observed. ULSC showed no group differences after dressing time and body size adjustments. Patients with HF had higher Borg scores than did HCs (NO-HF, P < 0.001; R-HF, P = 0.028). Conclusions Despite being low-intensity, dressing was associated with measurable physiological and subjective HF responses. R-HF trended toward slower HR recovery; NO-HF demonstrated consistently higher HR levels and perceived exertion. Monitoring recovery responses and supporting pacing and symptom self-monitoring during daily activities may be important in HF nursing care.